From shifting cultivation to teak plantation: effect on overland flow and sediment yield in a montane tropical catchment - Ribolzi, Olivier; Evrard, O.; Huon, S.; Rouw, Anneke de; Silvera, N.; Latsachack, K.O.; Soulileuth, B.; Lefevre, I.; Pierret, A.; Lacombe, Guillaume; Sengtaheuanghoung, Oloth; Valentin, Christian (Springer, 2016)
Soil erosion supplies large quantities of sediments to rivers of Southeastern Asia. It reduces soil fertility of agro-ecosystems located on hillslopes, and it degrades, downstream, water resource quality and leads to the siltation of reservoirs. An increase in the surface area covered with commercial perennial monocultures such as teak plantations is currently observed at the expanse of traditional slash-andburn cultivation systems in steep montane environments of these regions. The impacts of land-use change on the hydrological response and sediment yields have been investigated in a representative catchment of Laos monitored for 13 years. After the gradual conversion of rice-based shifting cultivation to teak plantation-based systems, overland flow contribution to stream flow increased from 16 to 31% and sediment yield raised from 98 to 609 Mg km-2. This result is explained by the higher kinetic energy of raindrops falling from the canopy, the virtual absence of understorey vegetation cover to dissipate drop energy and the formation of an impermeable surface crust accelerating the formation and concentration of overland flow. The 25-to-50% lower 137Cs activities measured in soils collected under mature teak plantations compared to soils under other land uses illustrate the severity of soil erosion processes occurring in teak plantations.